Testing a Family-centered Intervention to Promote Functional and Cognitive Recovery in Hospitalized Older Adults - Boltz, Marie (J Am Geriatr Soc, 2014)
A comparative trial using repeated measures design evaluated the feasibility and outcomes of the Family-centered Function-focused Care (Fam-FFC) intervention intended to promote functional recovery in the hospitalized older adult. A three component intervention (1) environmental assessment/ modification, 2) staff education, 3) family/patient education and partnership in care planning with post-acute follow-up) was implemented by a family-centered resource nurse and a facility champion. Control units were exposed to function-focused care education only. Ninety-seven dyads of medical patients age 65 and older and family caregivers (FCGs) were recruited from three medical units of a community teaching hospital. The majority of patients were female (53%); white (89%), married (51%) or widowed (40%), with a mean age of 80.8 (± 7.5). The majority of FCGs were married (78%) daughters (34%), followed by female spouses/partners (31%), in the age range of 46–65 (38%). Outcomes for patients included: functional outcomes (ADL and walking performance, gait, balance), and delirium severity and duration. FCG outcomes included preparedness for caregiving, anxiety, depression, role strain, and mutuality. The intervention group demonstrated less severity and duration of delirium, and better ADL and walking performance, but not gait/balance as compared to the control group. FCG who participated in Fam-FFC showed a significant increase in preparedness for caregiving, less anxiety and less depression from admission to two months post-discharge, but no significant differences in strain and mutuality, as compared to FCG in the control group. Fam-FFC is feasible and has the potential to improve outcomes for hospitalized older adults and family caregivers.